Improving the Business and Investment Climate in Indonesia - Moccero, Diego (OECD Publishing, 2008)
Indonesia's business environment is discouraging entrepreneurship and holding back private-sector growth and development. Weaknesses in the regulatory framework, infrastructure bottlenecks and poor governance continue to weigh down on investment. Policies have been put in place to address these problems, but much remains to be done. An important recent initiative is the enactment of the Investment Law in 2007, which strengthened the foreign investment regime. This paper argues that options for reform could focus on making regulations more pro-business, including by removing red tape and onerous provisions at the local level of government, improving governance and relaxing remaining restrictions on foreign investment. Further financial deepening would facilitate access by enterprises to more abundant, cheaper sources of finance. This Working Paper relates to the 2008 OECD Economic Assessment of Indonesia (www.oecd.org/eco/surveys/indonesia)
Keywords: Economics; Indonesia